Factors Influencing Students’ Creative Thinking Skills - Muhammad Anas; Akhmad Harum; Rusmayadi Rusmayadi (Universitas Negeri Makassar, 2023)
The study aims to get the description of creative thinking skills, self-perception, and motives of personal actualization of students at the PPB FIP program and to examine the influence of self-perception and self-actualization motives (either independent or mutual ) on the student's creative thinking skills. This is a quantitative study with an ex post facto design. We involved 143 students selected using a randomized proportional method. Data were collected using a scale and were analyzed descriptively and inferentially using regression analysis. The findings are: (1) the student's creative thinking skills are generally rather low, while their personal perceptions are less positive, and students' self-actualization motivations are rather low. (2) self-perception positively influences students' creative thinking skills, (3) self-actualization positively influences students' creative thinking skills, and (4) self-perception and self-actualization (simultaneously) influence the creative thinking skills of PPB FIP students.